2020
DOI: 10.5194/angeo-38-919-2020
|View full text |Cite
|
Sign up to set email alerts
|

Dust sputtering within the inner heliosphere: a modelling study

Abstract: Abstract. The aim of this study is to investigate through modelling how sputtering by impacting solar wind ions influences the lifetime of dust particles in the inner heliosphere near the Sun. We consider three typical dust materials, silicate, Fe0.4Mg0.6O, and carbon, and describe their sputtering yields based on atomic yields given by the Stopping and Range of Ions in Matter (SRIM) package. The influence of the solar wind is characterized by plasma density, solar wind speed, and solar wind composition, and w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…These estimates are based on dust sublimation; however, an additional destruction process recognized in the innermost parts of the solar system is sputtering by solar wind particles. Baumann et al (2020) showed that sputtering is more effective during a CME event than during other solar wind conditions and suggested that multiple CMEs can lead to an extension of the DFZ. Dust destruction near the Sun releases molecules and atoms, where photoionization, electron-impact ionization, and charge exchange quickly ionize the atoms and molecules.…”
Section: Dust Populations In the Inner Heliospherementioning
confidence: 99%
“…These estimates are based on dust sublimation; however, an additional destruction process recognized in the innermost parts of the solar system is sputtering by solar wind particles. Baumann et al (2020) showed that sputtering is more effective during a CME event than during other solar wind conditions and suggested that multiple CMEs can lead to an extension of the DFZ. Dust destruction near the Sun releases molecules and atoms, where photoionization, electron-impact ionization, and charge exchange quickly ionize the atoms and molecules.…”
Section: Dust Populations In the Inner Heliospherementioning
confidence: 99%